Contextualizing marital dissatisfaction: examining profiles of discordant spouses across life domains - Regan, Annie; Walsh, Lisa C.; Horton, Calen; Rodriguez, Anthony; Kaufman, Victor A. (Frontiers in Psychology, 2025)
Research suggests that up to a third of married individuals report low marital satisfaction, underscoring the importance of studying unhappy marriages. Although numerous studies have investigated the causes and consequences of marital dissatisfaction, less is known about the potential heterogeneity among individuals within unhappy marriages and the extent to which some unhappily married spouses may be satisfied in other life domains. The present study sought to determine whether categorical differences exist among unhappily married individuals. Using friendship satisfaction, family satisfaction, and life satisfaction as indicator variables, we conducted a latent profile analysis (LPA) on married individuals (N = 1,070). Specifically, we conducted LPA on subsets of participants reporting the lowest 20%, 22.5%, 25%, 31%, and 34% of marital satisfaction in our sample to ensure that our results were not specific to only the most dissatisfied spouses. We identified two distinct profiles of discordant marriages in all data subsets, with one profile reporting dissatisfaction in all areas, and the other reporting low marital satisfaction but close to average satisfaction with life, family, and friends. Our results emphasize that unhappy spouses are not monolithic, and that some individuals remain relatively satisfied in other life domains.